Numerical simulation of two-fluid flow and meniscus interface movement in the electromagnetic continuous steel casting process - Wiwatanapataphee, B.; Mookum, T.; Wu, Yong Hong (American Institute of Mathematical Sciences, 2011)
This paper presents a mathematical model and numerical technique for simulating the two-fluid flow and the meniscus interface movement in the electromagnetic continuous steel casting process. The governing equationsinclude the continuity equation, the momentum equations, the energy equation, the level set equation and two transport equations for the electromagnetic field derived from the Maxwell’s equations. The level set finite element method is applied to trace the movement of the interface between different fluids. In an attempt to optimize the casting process, the technique is then applied to study the influences of the imposed electromagnetic field and the mould oscillation pattern on the fluid flow, the meniscus shape and temperature distribution.